A Chinese version of the revised Fibromyalgia Impact Questionnaire: A validation study. (19th October 2022) - Li, Yan‐ting; Jiang, Quan; Jia, Yuan; Zhang, Yong‐feng; Xiao, Yu‐ya; Wang, Hui; Zhao, Ya‐yun; Jiao, Juan
Abstract: Objective: The revised Fibromyalgia Impact Questionnaire (FIQR) was developed to measure the quality of life of patients with fibromyalgia in randomized controlled trials and routine care. The purpose of this study was to translate and adapt the FIQR from English to Chinese, and to examine the validity and reliability of the Chinese version of the FIQR (CFIQR). Methods: Following the translation of the FIQR, fibromyalgia patients from 6 centers were recruited and completed the CFIQR, the validated Chinese version of the Medical Outcome Study Short Form 36 Health Survey (SF‐36) and the Beck Depression Inventory (BDI). In this study, Cronbach's alpha coefficient, test–retest reliability and item total correlation were used for evaluating external and internal reliability; and criterion and structural validity were evaluated. Results: A total of 200 fibromyalgia patients completed the study. The internal consistency was excellent (Cronbach's alpha .90, .88, .88 and .93 for function, overall impact, symptoms scales and total score, respectively; item‐total correlations from .25 to .83.) Test–retest reliability levels of the CFIQR total and subscale scores were strong correlation (intraclass correlation coefficient >0.75). Furthermore, there were significant correlations between the 3 subscale and the total score of the CFIQR and the SF‐36, as well as the CFIQR and the BDI, by criterion validity ( P  < .01). Confirmatory factor analysis gave an acceptable value for structural validity according to the 3‐factor structures of function, overall impact and symptoms. Conclusions: The CFIQR is a valid and reliable instrument for both clinical practice and research purposes with Chinese speakers globally. [ClinicalTrials.gov : NCT03381131].